Perancangan Sequence Triwulan Ketiga Penambangan Batubara pada PT Garda Tujuh Buana Tbk Provinsi Kalimantan Utara - Febrianto Wajar, Kurniawan; Thamsi, Alam Budiman; Chalik, Citra Aulian (CV Insight Publisher, 2023)
Mine design facilitates the achievement of the desired production target and provides an overview of the mining progress plan for a period of time. The purpose of this study is to determine the mining sequence design and production scheduling obtained by using data processing software and mine planning software, namely minescape software used for pit design design. The pit design is based on the results of geometric analysis, assuming that the mine is theoretically free from landslides with a slope height of 10 m, a slope width of 5 m, and a slope inclination of 45°. The area of the pit design in the third quarter is 26.76 hectares and the total coal amounted to 866,887.38 tons. For the third quarter production scheduling, for coal loading, 4 digging tools will be operated serving 43 loading tools with a total production of 284,939.12 tons with total working hours of 305.65 hours. So the estimated plan for 4 digging tools and 43 loading tools can meet the production target of the sequence design that has been made.